(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Introduction The Argentine Continental Margin (ACM), one of the largest margins worldwide, shows varied geotectonic and morphosedimentary settings (Fig. 1) with a complex oceanographic configuration (Fig. 2), as a consequence of the highly energetic oceanographic framework (Hastenrath, 1982; Berger and Wefer, 1996; Wefer et al., 1996, 2004; Mata et al., 2001; Bryden and Imawaki, 2001; Talley, 2003; Carter and Cortese, 2009). These configurations produce a complex sediments dynamic resulting from two major processes: the formation of nepheloid layers with an enormous amount of suspended sediments (Ewing et al., 1971; Biscaye and Eittreim, 1977; Emery and Uchupi, 1984; Bearmon, 1989; Scholle, 1996) and the activity of very strong bottom currents with high capacity for producing energetic erosive and depositional processes affecting the sea floor. The result of these sets of conditions is responsible of the unusual high sand content of this margin in relation to others in the world (Lonardi and Ewing, 1971; Frenz et al., 2004; Bozzano et al., 2011). Although the margin has been studied since mid XX century (Heezen and Tharp, 1961, in Heezen, 1974; Ewing et al., 1964; Ewing, 1965; Ewing and Ewing, 1965; Ewing and Lonardi, 1971; Lonardi and Ewing, 1971; Le Pichon et al., 1971; Urien and Ewing, 1974; Mouzo, 1982; Emery and Uchupi, 1984; Pudsey et al., 1988; Lawver et al., 1994; Parker et al., 1996, 1997; Coren et al., 1997; King et al., 1997; Gilbert et al., 1998; Pudsey and Howe, 1998), an exhaustive analysis of the sedimentary processes involved in its evolution is a still pending issue. However, recent studies carried out since the beginning of the XXI century with the pioneering works by Pudsey and Howe (2002) and Cunningham et al. (2002) in the Scotia Sea, and Hernández Molina et al. (2009) in the passive sector of the margin, initiated the epoch of more specific investigations that led to revisit most of the concepts concerning the deepsea sedimentation previously considered. The objective of this contribution is to synthesize the present knowledge on deep sedimentary processes in the ACM, previously discussing the change from the “turbiditic” to the “contouritic” models that took place as a result of the studies performed in the region during the last 30 years. This change followed the advance in the conception of deepmarine sedimentary processes that occurred worldwide, as expressed by Swallow and Worthington (1957), Stommel (1958), Heezen and Hollister (1964), Hollister (1967), Shanmugan (2000), Stow et al. (2002), Mc.Cave (2002), Rebesco and Camerlenghi (2008), Hsü (2008) and Rebesco et al. (2014), among others. Argentine Continental Margin (ACM): state of the art The first reference to the sedimentary processes acting in the slope and rise of the ACM was done by Ewing et al. (1964), who stressed the relevance of submarine canyons and nepheloid layers as the main ways of transport of fine sediments to the deep regions, being pelagic sedimentation of minor importance. Only in the abyssal plains those authors mentioned the possibility of bottom currents acting on the sea floor. Later contributions by Le Pichon et al. (1971), Lonardi and Ewing (1971) and Ewing and Lonardi (1971) reinforced those concepts and mentioned the bottom currents forming the drifts (contouritic bodies) in the Argentine Basin. Although some subhorizontal terraces were later described in the middle slope by Lonardi and Ewing (1971) and Ewing and Lonardi (1971), the consideration of the continental slope as a highgradient feature mostly erosive and dominated by turbiditic processes still prevailed at those times (Heezen and Tharp, 1961, en Heezen, 1974; Emery and Uchupi, 1984) (Fig. 3), even if Wüst (1957, in Heezen 1973) had previously noticed that strong bottom currents swept the continental slope of eastern South America. Moreover, as shown for example by Ewing and Lonardi (1971) and Pudsey and Howe (2002), sea floor photographs taken in the decades of 19601970 in the Argentine margin (GeoMapApp, 2013) already illustrated unidirectional ripples in the slope (Fig. 4). The advance in the knowledge and application of the new models proposed at those times in the world, led to the first mention to contouritic deposits in the ACM by Pudsey et al. (1988) in the Scotia Sea and surroundings, followed by new findings in the region by Lawver et al. (1994), Coren et al. (1997), King et al. (1997), Gilbert et al. (1998), Pudsey and Howe (1998, 2002), Cunningham et al. (2002), Maldonado et al. (2003, 2006) and Koenitz et al. (2008). Later contributions by Rovira et al. (2013), Esteban (2013), Pérez (2014) and Pérez et al. (2015) improved the knowledge in those areas. In the passive margin, Hernández Molina et al. (2009) described for the first time the very extensive and complex Contourite Depositional System (CDS) developed along 1600 km. Following this, the contributions by Hernández Molina et al. (2010, 2011), Violante et al. (2010b), Bozzano et al. (2011), Gruetzner et al. (2011, 2012, 2016), Lastras et al. (2011), Muñoz et al. (2012) and Preu et al. (2012, 2013) provided more detailed information about the CDS in some localized areas of the margin. The development of the concept of contouritic sedimentation in the ACM was necessarily related to the consideration that alongslope deep marine sedimentary processes are closely linked to the activity of bottom currents interacting with the seafloor. Taking into account the particularly energetic ocean dynamic in the region and the strong thermohaline stratification (Reid et al. 1977; Piola and Gordon, 1989; Bianchi et al., 1993; Saunders and King 1995; Boebel et al., 1999; Arhan et al. 1999, 2002a, 2002b, 2003; Piola and Matano 2001; Bianchi and Gersonde, 2002; Henrich et al. 2003; Carter et al. 2008), and considering that this oceanographic structure evolved since EoceneOligocene times (Hinz et al., 1999; Zachos et al., 2001; Lawver and Gahagan, 2003; Livermore et al., 2004; Cavallotto et al., 2011; García Chapori, 2015), it is easy to understand that the sedimentary architecture and the morphosedimentary configuration of the margin strongly responded to the impact of bottom currents on the seafloor acting along large periods of time, so shaping the continental margin (Pudsey and Howe, 2002; Cunningham et al., 2002; Hernández Molina et al., 2009, 2010, 2011; Violante et al., 2010 b; Lastras et al., 2011; Muñoz et al., 2012; Preu et al., 2012, 2013; Gruetzner et al., 2011, 2012, 2016; Pérez et al., 2015). However, the above mentioned processes varied regionally depending on the geotectonic fra mework of the margin, which is composed of four types of margins (Pelayo and Wiens, 1989; Ramos, 1996; Hinz et al., 1999; Mohriak et al., 2002; Franke et al. 2007, 2010; Cavallotto et al., 2011; Violante et al., 2017) (Fig. 1): passive, transcurrent, mixed and active. Consequently, and according to the entire set of factors involved in different regions of the margin (geotectonic, morphological, sedimentary, oceano graphic, etc.) and their regional variations, six zones are identified from north to south (Fig. 5). Five of them correspond to the passive margin and one encompasses the transcurrent, mixed and active margins. Northeastern Buenos Aires (36-38°S). Large subma rine canyons and masstransport deposits shaping the slope, as well as an extensive rise, are the major features in this region. The largest canyons systems are Rio de la Plata and Mar del Plata, which were previously described by different authors (Lonardi and Ewing, 1971; Ewing and Lonardi, 1971; Violante et al. 2010 a; Bozzano et al., 2011; Krastel et al. 2011; Preu et al. 2012, 2013; Voigt et al. 2013, 2016). Dominant processes are gravitational, producing tur biditic and masstransport deposits, with contouritic drifts in the terraces between canyons. Major terraces are La Plata (T1, at 500–600 m depth), Ewing (T2, at 12001500 m), T3 (restricted to the northern flank of the Mar del Plata canyon at 2500 m) and Necochea (T4, at 3500 m) (Hernández Molina et al., 2009; Preu et al., 2013). Drifts are plastered and mounded in the Ewing terrace and plastered to detached in the Necochea terrace. The rise is wide as a result of the highly sig nificant downslope processes. Contouritic drifts are 700 to 1000 m thick and are composed of gravelly, sandysilty and muddy facies. This zone extends northwards towards the Uruguayan margin (Franco Fraguas et al., 2014, 2016; HernándezMolina et al., 2015). Southeastern Buenos Aires (38-40°30’S). Dominant morphological elements in the slope are contouritic terraces (the same that in the northern region), which are affected, and partially interrupted, by small submarine canyons. The rise in this region is progressively reduced in size towards the south. Several contouritic drifts (plastered) have been described (HernándezMolina et al., 2009; Violante et al., 2010 b; 2012; Bozzano et al., 2011; Preu et al., 2012, 2013; Gruetzner et al., 2016). La Plata and Ewing contouritic terraces show their largest development here, with drift’s thicknesses up to 1 km. Despite the small size of submarine canyons, they seem to play a significant role in transporting sediments offshore as evidenced by large turbiditic lobes and masstransport deposits present at the base of the slope, although they show reoriented patterns to the northeast due to the strong activity of northward flowing deep contouritic currents, so constituting mixed features where detached drifts are recognized (Hernández Molina et al., 2009). Northern Patagonia (40°30’-42°30’S). Contouritic terraces dominate the landscape of the slope in this region, although they are highly dissected by a dense net of small submarine canyons; a narrow rise is present in this region. Contouritic drifts are plastered and mounded (Hernández Molina et al., 2010; Gruetzner et al., 2016), with thicknesses up to 1600 m and a sandymuddy texture. However, gravitational processes are also important as eviden ced by the significance of slides and masstransport deposits in the middle slope, rise and western flank of the Argentine Basin (Hernández Molina et al., 2009; Bozzano et al., 2014; Costa et al., 2014). Central-northern Patagonia (42°30’-46°S). The most impressive features in this region are the large Sub marine Canyons Systems Ameghino and Almirante Brown, which are the largest canyons in the ACM. They are transverse to the slope in their upper and middle sections, but in the midlower slope they run parallel to the isobaths. Although tectonic processes have been considered for explaining the change in the canyon’s direction (Rosello et al., 2005), recent studies indicate the strong influence of alongslope currents able to deflect the canyons to the north (Hernández Molina et al., 2009; Lastras et al., 2011; Muñoz et al., 2012). Where contouritic drifts were recognized around the canyons, they are dominantly plastered with thickness up to 1600 m. Central-southern Patagonia (46-49°S). Very large contouritic terraces develop here, shaping four major terraces (Nágera, at 500 m depth, Perito Moreno, at 1000 m, Piedra Buena, at 2100–2500 m and Valentín Feilberg, at 3500–4000 m) (Hernández Molina et al. 2009, 2010; Gruetzner et al., 2011). They are composed of thick (up to 2000 m) plastered drifts that became mounded towards the deeper terrace. Contouritic processes are so important here that even the rise acquires a “contouritic” character rather than a typical baseofslope gravitational feature. Southern Patagonia, islands and Scotia Arc (south of 49°S). Comprises the entire region that corresponds to the transcurrent, mixed and active margins, where more detailed studies are still lacking for differentiating sectors with distinct morphological and genetic characteristics. The configuration of this zone favors the occurrence of very significant gravitational processes in the steeper sectors of the slope both in the northern (Escarpa de Malvinas –Malvinas Scarp) and in the southern side (flank of the Dorsal Norte de Scotia North Scotia Ridge). In the western side of the Arc, Lonardi and Ewing (1971) described at least seven submarine canyons. Contouritic drifts develop locally in the slope, and within depressions between structural heights and seafloor elevations, where more energetic bottom currents are channeled. This is the case for the Fosa de Malvinas (Malvinas Trough) and for different passages connecting the Scotia Sea with the southwestern sector of the Argentine Sea (Cunningham et al. 2002; Pudsey and Howe, 2002; Rebesco et al., 2002; Maldonado et al., 2003, 2006, 2010; Koenitz et al., 2008; Baristeas et al., 2013; Rovira et al., 2013; Esteban, 2013; Pérez, 2014; Pérez et al., 2015). Contouritic drifts in these regions are mainly plastered, although mounded, elongated, detached and sheeted types are also recognized depending on their location and local morphology. Concluding remarks The progress in the scientific knowledge of the deepsea sedimentation in the ACM has significantly advanced in recent years, through the change from a “gravity, densitydominated” model to an “along slope, currentdominated” model. However, it must be considered that the two models are not opposite, but they coexist and interact. Two major areas can be differentiated in terms of the prevalent sedimentary processes. The passive margin is dominated by an extensive Contouritic Depositional System, whose complex architecture is characterized by a variety of depositional, erosive and mixed features interacting with large systems of submarine canyons and mass transport processes, with different configurations according to the zone and local morphosedimentary characteristics. On the other hand, in the transcur rent, mixed and active margins, contouritic drifts are regionally limited and in general located in more energetic regions such as passages between structural heights and seafloor elevations. The advance in the knowledge and the under standing of the deepsea processes in the ACM is not only relevant for the development of marine geological and sedimentological sciences but also in the field of Physical Oceanography. The study of contouritic bodies and their records is also useful for paleoenvironmental and paleoceanographic re constructions. Applied aspects such as resources exploration, seafloor instabilities, deep currents and their interaction with sea bed, as well as other items related to marine geohazards, will benefit from the integration between Marine Geology and Oceanography.